Gender-specific patterns of muscle imbalance in elite badminton players: A comprehensive exploration - Gasibat, Qais; Abdullah, Borhannudin; Samsudin, Shamsulariffin; Dan, Iulian Alexe; Alexe, Cristina Ioana; Tohănean, Dragoș Ioan (Multidisciplinary Digital Publishing Institute, 2023)
The high-intensity demands of overhead sports exert significant stress on the bilateral shoulder complex, triggering adaptive kinematics and a distinct strength imbalance between internal and external rotators. The imbalance being referred to in the given statement poses a potential risk for humeral head displacement and puts nearby tendons under tension, heightening the vulnerability to injury. This study aims to assess muscle imbalances in badminton athletes. The first hypothesis (H1) suggests that there are differences in internal and external shoulder rotation movements between dominant and non-dominant segments in badminton players. The second hypothesis (H2) proposes that there are variations in muscle imbalances based on gender among elite badminton players. The objectives are to analyze these differences and explore potential gender-related variations in muscle imbalances. The study seeks to contribute to the understanding of muscle imbalances in badminton athletes and potentially guide training and injury prevention strategies in the sport. Using a cutting-edge Hand-Held Dynamometer (HHD), a cohort of 30 elite badminton players underwent an assessment to uncover any bilateral shoulder rotation strength imbalances during a challenging five second isometric maximum contraction. The participants boasted an average age of 17.4 years and a mean playing experience of 7.23 years. The study revealed a notable difference in the ratio of external and internal strength between the dominant and non-dominant shoulders (p = 0.000). This discrepancy amounted to a striking 27.93% muscle imbalance in external rotation/internal rotation strength ratios, favoring the dominant shoulder. Moreover, gender-specific differences were detected, with male players exhibiting a 24.54% muscle imbalance in favor of the dominant shoulder, while female players showcased a more substantial 31.33% imbalance (p = 0.000). In light of these findings, it became evident that elite badminton players possess considerably stronger dominant shoulders compared with their non-dominant counterparts. Furthermore, the study revealed that male players experience less muscular imbalance than their female counterparts.